Stability Of a Quadratic Functional Equation in Intuitionistic Fuzzy Banach Spaces - Pratap Mondal; Nabin Chandra Kayal; T K Samanta (Journal of New Results in Science)
Hyers-Ulam-Rassias stability theorem has been applied to several functional equations for studying stability in caseof approximation of a given functional equation in Banach spaces,fuzzy Banach spaces etc. In this paper, we wish to study generalized Hyers-Ulam-Rassias stability regarding the approximationof the following quadratic functional equationf(2x + y) − f(x + 2y) = 3f(x) − 3f(y) (1)in intuitionistic fuzzy Banach spaces.